2018
DOI: 10.1176/appi.ps.201700562
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Prescribing to Adolescents in the United States From 2005 to 2016

Abstract: The 2-3 days' supply decreased from 50.5% (2005) to 36.7% of fills (2016), while 4-5 days' supply increased from 30.2% to 37.7%. Fills of 6-7 and 8-15 days increased slightly. Fills of over 30 days remained near 0.0%, and one-day fills remained at 1.0-2.0% until 2016, when they increased to 3.6% Conclusions: For adolescents, fills of prescription opioids generally exceeded three days. Efforts to reduce opioid prescribing through guidelines, prescription drug monitoring programs, and limits on days' supply do n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…In 2016, there was a substantial increase in 1-day opioid prescriptions. 50 These trends mirror the nation's opioid epidemic. In a large retrospective analysis of opioid-naive postoperative patients, Harbaugh et al 51 found that opioid use persisted (prescriptions filled >90 days' postoperation) in 5% of patients (4267 patients), ranging from 2.7% to 15.2% across surgical procedures.…”
Section: Social and Economic Risk Factors To Adolescent Opioid Misusementioning
confidence: 99%
“…In 2016, there was a substantial increase in 1-day opioid prescriptions. 50 These trends mirror the nation's opioid epidemic. In a large retrospective analysis of opioid-naive postoperative patients, Harbaugh et al 51 found that opioid use persisted (prescriptions filled >90 days' postoperation) in 5% of patients (4267 patients), ranging from 2.7% to 15.2% across surgical procedures.…”
Section: Social and Economic Risk Factors To Adolescent Opioid Misusementioning
confidence: 99%
“…[14][15][16][17][18][19]40 Earlier studies of trends in opioid prescribing among adolescents and younger adults have found stable or decreasing opioid prescribing rates within the past several years and decreases in long-duration prescriptions, although, to our knowledge, no studies have examined trends in high-risk opioid prescribing practices. [22][23][24]41 Our findings might reflect changing norms about opioid prescribing, related to policy changes for adults, such as the publication of the Centers for Disease Control and Prevention guideline for prescribing opioids for chronic pain published in 2016, 31 which states that clinicians should prescribe the lowest effective dose and duration of opioids, as well as state legislation limiting duration and amount of opioid prescribed. 25 Opioid prescribing guidelines and efforts focused on deprescribing for adolescents and younger adults at risk for opioid dependence are important strategies to reduce unnecessary prescription opioid use.…”
Section: Discussionmentioning
confidence: 86%
“…[20][21][22][23] One study in adolescents assessed trends in prescription duration, showing a decrease in short-duration prescriptions. 24 However, to our knowledge, no US populationbased studies have provided a comprehensive look at trends in opioid prescribing practices, including amount prescribed, duration, high-dosage, and ER/LA prescriptions, in the pediatric, adolescent, and younger adult populations.…”
mentioning
confidence: 99%
“…42 At least five states have also placed specific restrictions on daily dosages, and specific restrictions on prescribing for minors. 43 Although these prescribing limits were also enacted with other regulatory efforts directed at opioid prescribing, such as prescription monitoring programs (PMPs), and first-responder naloxone training, 44 restricting opioid prescribing appears to be an important facet of a multi-pronged policy approach to reducing prescription opioid-related misuse, dependence and overdose death. A decline in opioid prescribing since 2011 has coincided with a steep decline in opioid analgesic misuse, and a two-year (2012-2013) decline in the rate of prescription opioid overdose deaths.…”
Section: State and Local Responsesmentioning
confidence: 99%